2020
DOI: 10.1589/jpts.32.292
|View full text |Cite
|
Sign up to set email alerts
|

Posterior thigh thermal skin adaptations to radiofrequency treatment at 448 kHz applied with or without Indiba<sup>®</sup> fascia treatment tools

Abstract: This study aimed to evaluate the posterior thigh's skin thermal responses to 448-kHz radiofrequency-based therapy applied either in the form of standard application (Indiba ® Activ) or combined soft tissue treatment (Indiba ® Fascia treatment). [Participants and Methods] Ten healthy males (22 ± 3 years of age, weight 75.2 ± 4.9 kg, height 178.5 ± 4.7) received four different treatments which included a) Indiba ® Activ (IA) radiofrequency treatment, b) Indiba ® Fascia (IF), c) Indiba ® Activ placebo (IAP) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…In turn, Fousekis et al valued the thermal reaction of the skin of the posterior part of the thigh to the therapy based on a radio frequency of 448 kHz in a postmortem sample, which was applied in the form of a standard application (Indiba ® Activ) or combined soft tissue treatment (Indiba ® Fascia procedure) in a total of nine healthy men (age 22 ± 3 years, body weight 75.2 ± 4.9 kg, height 178.5 ± 4.7). In conclusion, these researchers found that the application of CRET at 448 kHz can induce and maintain significant thermal adaptations of the skin, reflecting increased blood circulation and the metabolism of underlying tissues, which seems to be in line with our results [ 50 ]. Moreover, López-de-Celis also assessed the effectiveness of CRET in a postmortem sample ( n = 10).…”
Section: Discussionsupporting
confidence: 92%
“…In turn, Fousekis et al valued the thermal reaction of the skin of the posterior part of the thigh to the therapy based on a radio frequency of 448 kHz in a postmortem sample, which was applied in the form of a standard application (Indiba ® Activ) or combined soft tissue treatment (Indiba ® Fascia procedure) in a total of nine healthy men (age 22 ± 3 years, body weight 75.2 ± 4.9 kg, height 178.5 ± 4.7). In conclusion, these researchers found that the application of CRET at 448 kHz can induce and maintain significant thermal adaptations of the skin, reflecting increased blood circulation and the metabolism of underlying tissues, which seems to be in line with our results [ 50 ]. Moreover, López-de-Celis also assessed the effectiveness of CRET in a postmortem sample ( n = 10).…”
Section: Discussionsupporting
confidence: 92%
“…This temperature increase is not limited to the surface and has been recorded up to 20 mm deep [ 26 ]. In another test, these skin temperature changes were recorded up to 164 min later [ 28 ]. A higher oxyhaemoglobin concentration had been reported when applying heat through CRET than by surface heat, with a difference of up to 9% and higher ranges (56.3–77.9 vs. 48.2–74.0 µmol/L) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capacitive-resistive electrothermal therapy (CRET) is based on the non-invasive application of 0.45–0.60 MHz radiofrequency (RF) currents that, when circulating through the treated tissues, causes a temperature increase due to ion reorientation and friction ( 1 ). This therapy has been applied successfully for skin, muscle and osteoarticular tissue repair ( 2 , 3 ), as well as for the treatment of arthritis ( 4 ), Peyronie's disease ( 5 ) and ailments involving poor blood flow ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%